Representation of Gender Stereotyping in Louisa May Alcott’s Little Women: Endorsement of Traditional Gender Roles - Nabilla Rahmadhiya Ekasanti; Mala Hernawati (Universitas Gadjah Mada, 2019)
This research discusses how the characters in the novel Little Women written by Louisa May Alcott eventually submit themselves to the stereotypical role of women in the late 19th century when in reality American women were protesting the ideology of ‘separate spheres’ in accordance to the traditional gender stereotype that they faced. The research applies the sociological approach to uncover the connection between the literary work and the social condition of the era and to find out how the gender roles affect the characters of the March girls, supported by the theory of children literature. The primary data used in this research are the excerpts taken from Louisa May Alcott’s Little Women and some supporting data are taken from academic journals. The research focuses on the characters of the March Girls’ actions and dialogues that show submissive behavior, in contrast to the efforts and movement of the women during that era who were protesting the ideology of ‘separate spheres’ that resulted in inequality. The result of the research concludes that Little Women seems to be written only as a reproduction of traditional gender values, this matter contradicts with what the American women in the late 19th century struggled for.